Social capital and territorial development in Serra do Brigadeiro, Minas Gerais, Brazil - Ferreira de Freitas, Alair; Ferreira de Freitas, Alan; Alves Junior, Almiro (Cooperativismo & Desarrollo, 2021)
This work aimed to understand how the dynamics of local interaction can condition the format of implementation of public policies, specifically the National Rural Development Program - PRONAT. In order to do this, we tried to verify which elements interfere in the options of the local actors in relation to their engagement in the network of organizations that operate the program and used a case study in the Serra do Brigadeiro Territory, Minas Gerais-Brazil, and data Acquired through interviews. It was found that the engagement of local organizations is dependent on their profile and organizational history. The union organizations that have experienced the community organization work of the Catholic Church have been able to expand their networks and expand their focus, incorporating work fronts beyond the social security issue, giving priority to access to many public. policies. It is concluded that the territorialisation of space and public policies depends on the organizational arrangements and prevailing institutions, on the way in which actors interact with each other and reproduce power relations.
Keywords: territory; social capital; public policies; network